PENGARUH FINANCING TO DEPOSITE RATIO DAN NET PERFORMING FINANCING TERHADAP RETURN ON ASSETS PADA BANK MUAMALAT TBK PERIODE TAHUN 2011-2020 - Jannatul Jannatul; Abd. Malik; Ahsan Putra Hafiz (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research is motivated by the existence of obstacles to oil palm farming which are thought to have an impact on the welfare of oil palm planters in Teluk Bawah Village, Cermin Nan Gedang District, Sarolangun Regency, namely the lack of implementation of planning in the process of maintaining oil palm and which greatly influences the welfare of oil palm planters. This research is a type of quantitative research. The results of this research are: From the results of the regression test, it was found that maintenance costs have no effect on the welfare of oil palm farmers in Teluk Bawah Village, Cermin Nan Gedang District, Sarolangun Regency. From the results of the regression test, it is known that productivity influences the welfare of oil palm farmers in Teluk Bawah Village, Cermin Nan Gedang District, Sarolangun Regency. Simultaneously, maintenance costs and productivity influence the welfare of oil palm farmers in Teluk Bawah Village, Cermin Nan Gedang District, Sarolangun Regency, UIN STS Jambi